Triple Helix Collaboration Model for Improving the Performance of Socio-Economic Empowerment Programs for Traditional Fishing Families in Medang Deras - Dara Aisyah; Muhammad Sontang Sihotang; M Deny Effendy Tambusay (Administratio, 2025)
Fishermen empowerment programs have thus far failed to sustainably improve the socio-economic conditions of fishing families. According to data from Statistics Indonesia (BPS) in 2023, the national poverty rate remains at 9.36%, far from the 0% poverty target set for 2024, with 70% of the poor population residing in coastal areas, most of whom are engaged in fishing. This failure is attributed to the government's lack of preparedness in understanding the actual conditions of coastal communities, as well as the absence of coordination with innovative university research in the design of empowerment programs. The gap between key actors has rendered intervention efforts less effective. This study aims to integrate the Triple Helix collaboration model as an innovative approach to improve the performance of socio-economic empowerment programs for traditional fishing families by utilizing local waste potential into calcium-based product innovation. The research was conducted in two hamlets of Nelayan Village, Medang Deras Subdistrict, Batubara Regency, North Sumatra, using a social engineering approach through the Participatory Action Research method over one year. The intervention involved mentoring and knowledge transfer through socialization, focus group discussions (FGDs), and training for fisher households. The findings show that the majority of fishers live in conditions of structural poverty, with daily incomes below IDR 50,000 and trapped in debt cycles with middlemen. The training and mentoring intervention on coastal waste processing into calcium-based product innovation successfully led to the formation of innovation-based fisher groups, formalized through the signing of an Institutional Arrangement (IA) with the subdistrict government, which was subsequently adopted as a policy. This study not only presents a contextually relevant collaborative model but also offers a prototype of an empowerment system that is collaborative, circular, and rooted in local needs and potential.